(untitled) (Malaysian Management Journal, 2007)
There has been considerable research establishing a link between cultural and sub-cultural values, and aspects of consumer behaviour. However, religion as a sub-cultural element has received little attention from researchers. This study sought to examine the influence of religiosity on one aspect of consumer behaviour – shopping orientation. The research data was collected by means of a survey through personal interviews using a structured questionnaire. Out of 300 respondents targeted, 226 questionnaires were deemed usable for statistical analysis. The findings revealed that three shopping orientation factors, namely quality consciousness, impulsive shopping, and price consciousness were related to religiosity. It is suggested that religiosity should be included as a possible determinant of shopping orientations in consumer behaviour models.